Research progress on electromagnetic spectrum multidimensional situation compressed mapping technology - Feng SHEN; Guoru DING; Jie LI; Bo ZHOU; Qihui WU (Tongxin xuebao, 2023)
In the increasingly complex electromagnetic spectrum environment, accurately obtaining comprehensive spectrum situation is a crucial prerequisite for making precise spectrum decisions.First, the spectrum mapping was introduced and compared with spectrum sensing.Then, an in-depth review of existing spectrum situation generation methods was conducted.Next, multidimensional spectrum situation compressed mapping in the face of challenges such as heterogeneity, large scale missing data, time variability and environmental complexity was proposed.It effectively compensated for the incompleteness of the spectrum mapping framework caused by ignoring the spectrum situation sensing process in traditional spectrum situation generation methods.This could further provide more accurate guidance for enhancing spectrum utilization efficiency, strengthening spectrum security maintenance, and intensifying electromagnetic warfare decision-making.Lastly, the future development trends of spectrum compressed mapping were discussed.